Meningkatkan Hasil Belajar Renang Gaya Bebas Melalui Model Pembelajaran Problem Bassed Learning Pada Siswa Kelas VII SMP Negeri 16 Ambon - J. Solissa; M. D. Hukubun; Muhammad Salman Iwan (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to examine the improvement of freestyle swimming learning outcomes through the problem-based learning model for seventh-grade students at SMP Negeri 16 Ambon. This study employed a classroom action research procedure conducted in a cyclical process, each cycle consisting of planning, implementation, observation, and reflection as a guideline for the research stages. The results of this study indicate that there was an analysis of the basic freestyle swimming movements in Cycle I, with an average student learning score in Cycle I, with 13 students completing the basic movement 59%, and 9 students not completing it 41%. Improvements in basic freestyle swimming movements in Cycle II showed significant improvement, as evidenced by the average student score, with 22 students achieving the Minimum Competency (KKM) in Cycle II. Based on the reflection data collected, the results of the classroom action research indicate that at the end of the cycle, there was an improvement in the quality of learning in basic freestyle swimming movements.